Programa inteligencia interpersonal “PEII” para mejorar el clima institucional docente de la I.E. n° 81526 “Víctor Ganoza Plaza” – Laredo, 2019 - Saucedo Ruiz, Herman (2021)
The purpose of this research work was to demonstrate that the application of the Educational Program based on Interpersonal Intelligence influences the improvement ofthe Institutional Climate of the teaching staff of Institución Educativa No. 81526 "Víctor Ganoza Plaza" Santo Domingo industry district Laredo. In carrying out the work will be featured a sample population consisting of 18 teachers working in the aforementioned Garden, which formed the experimental group with one group pre and post test,and the design of a pre-experimental research. The program included training of teachers in emotional competence in interpersonal intelligence following the approach of Goleman (2009). Which comprised workshops on empathy and social skills, various strategies for the implementation and enforcement of the program were used. The results confirm the research hypothesis that the educational program of interpersonal intelligence "PEII" influenced the improvement of the institutional climateof teachers in presenting highly significant differences between the results of the pretest and posttest.